Effects of infliximab biosimilar on retinal microvasculature in Crohn’s disease patients evaluated by optical coherence tomography angiography - Hesham M. El Mazar; El sayed E. El Shayeb; Asmaa M. Ebrahim; Ayatullah S.A. Motawe; Esraa S. El-Ghoubashy (Journal of the Egyptian Ophthalmological Society)
Objective To compare the retinal microcirculation in Crohn’s disease cases under infliximab (IFX) biosimilar with controls that are age- and sex-matched in terms of disease severity. Background Crohn’s disease is a relapsing, remitting condition that affects the gastrointestinal tract. One approach to management is to use biological therapy. Patients and methods This cross-sectional case-control study was carried out at the outpatient clinic of the gastroenterology and hepatology departments of the Faculty of Medicine at Menofia University and was imaged at Shebin Elkom Ophthalmology Hospital. The study included 60 participants who were divided into three groups with no ophthalmologic history or symptoms. Results Regarding slit examination findings, within group A 14 (70%) cases had eye dryness, and six (30) had allergic keratoconjunctivitis; within group B 11 (55%) cases were normal, five (25%) cases showed dryness, and three (15%) had allergic keratoconjunctivitis; and there was anterior uveitis in one (5%) patient; in group C 10 (50%) patients were normal, seven (35%) patients showed dryness, and three (15%) had allergic keratoconjunctivitis. There was a significant increase in dryness and allergic keratoconjunctivitis within group A compared with groups B and C (P=0.04). Conclusion Our study concluded that patients with moderate to severe Crohn’s disease who received IFX biosimilar had higher eye dryness, allergic keratoconjunctivitis, and longer disease duration. Therefore, the use of IFX should be limited.